FREQUENCY OF ANTI THYROID PEROXIDASE ANTIBODY IN PATIENTS OF VITILIGO: Patients of Vitiligo - ., Maj Ayesha Khokhar; Shaikh, Zafar Iqbal (Pakistan Armed Forces Medical Journal, 2013)
Objective: The objective of this study was to compare the frequency of anti thyroid peroxidase antibody in patients suffering from vitiligo with healthy control group.Type of Study: Case control study.Settings: Dermatology Department, Military Hospital, Rawalpindi, from 20th March 2010 to 20th July 2011.Material and Methods: Fifty clinically diagnosed patients of vitiligo, age ≥ 18 yrs and both genders with no history of thyroid disease, past or current use of drugs for thyroid disorder or thyroid surgery were included as cases (Group A). Fifty healthy individuals with no evidence of vitiligo or thyroid disorder on history and physical examination and with no family history of vitiligo, matched for age and gender with cases, were included as control (Group B). Serum anti thyroid peroxidase (anti TPO) antibodies were measured using enzyme linked immunosorbent assay (ELISA) in both cases and control.Results: Eight (16%) patients in Group A were anti-thyroid peroxidase antibody positive and forty two (84%) patients were negative while one (2%) patient was anti-thyroid peroxidase antibody positive in Group B and forty nine (98%) patients were negative (p = 0.001).Conclusion: Anti TPO antibody is significantly more common in patients of vitiligo as compared to general population.